Effect of Aluminum on Thermal Performance of Ceramsite and its Application - Liu, Fangliang; Wu, Weiwei (Asian Journal of Chemistry, 2014)
Thermal performance, such as the thermal resistance and thermal conductivity of ceramsite under the effect of aluminum, were measured. A holistic model was developed to measure the thermal performance. Different ceramsite insulation structures were selected for simulating and comparing. By simulating the holistic model, it was found that aluminum greatly promotes the thermal resistance of ceramsite to twice the thermal resistance of ceramsite. The average thermal conductivity of ceramsite under the effect of aluminum is decreased by 50 %. The marginal thermal resistance of the ceramsite insulation structure stuck on aluminum foil internally is almost the same as that of the widely used ceramsite hollow brick with EPS board and it is incombustible, which implies a better structure for architectural heat insulation.